Method considerations and study protocol for a Nordic multi‐centre prospective study on outcomes in rare paediatric epilepsy surgery subgroups. (8th February 2023) - Reinholdson, Jesper; Malmgren, Kristina; Chaplin, John; Olsson, Ingrid; Hallböök, Tove
Abstract: Epilepsy surgery is a therapeutic option for selected children with drug‐resistant epilepsy. Children who are surgical candidates have a high prevalence of neurodevelopmental comorbidities. There is a lack of adequately sized prospective studies in a number of rare surgical subgroups, especially of outcome domains such as cognitive level and health‐related quality‐of‐life. In this article, we describe method considerations and a study protocol for a Nordic population‐based multi‐centre follow‐up programme covering seizure as well as non‐seizure outcomes in children aged <4 years undergoing resective epilepsy surgery and children aged ≤18 years undergoing hemispherotomy, callosotomy or surgery for hypothalamic hamartoma.